-2+5(5-6x)=83

Simple and best practice solution for -2+5(5-6x)=83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+5(5-6x)=83 equation:



-2+5(5-6x)=83
We move all terms to the left:
-2+5(5-6x)-(83)=0
We add all the numbers together, and all the variables
5(-6x+5)-2-83=0
We add all the numbers together, and all the variables
5(-6x+5)-85=0
We multiply parentheses
-30x+25-85=0
We add all the numbers together, and all the variables
-30x-60=0
We move all terms containing x to the left, all other terms to the right
-30x=60
x=60/-30
x=-2

See similar equations:

| 12=18w-36=0 | | 21=-4x+8 | | 14x-1+9=9x-22 | | 6x+2=3(2x−1 | | 6(3x+6)+7(x+5)=46 | | b+9=17b= | | 3225+100x=1 | | 6c+8=-2+8c | | -8w=-10w-32 | | (2x+1)+(10x-10)+(3x+14)=180 | | 47x=34 | | 4(w+18)=4 | | 14=-3m-7 | | 3(4+7n)=-7+2n | | 3(x-4)=x-4+6x | | 4x+6=(3x+2) | | 18=-5(3-3k)-6(4K-1) | | 5x+2(x-6)-14=4(x+3) | | 4n-1=2n+11 | | 2(3x+11)=58 | | x2-x+14=2x(x-3) | | 40+22.50x=940 | | 4x+-10=46+13x | | 3(7x-7)-6=99 | | (x+20)+x+30=180 | | 4p+12=-8 | | s2=334 | | 6q+6=3q | | 8x+7=9x-9 | | T(x)=75x+759 | | -5(x+1)+3x=6-(4x-5) | | -8-b=12 |

Equations solver categories